Composite catalyst, preparation method thereof and application of composite catalyst in irradiation degradation of coal chemical sewage

By preparing composite catalysts of four metals, La, Co, Bi and Ti, using electron beam irradiation technology to efficiently degrade organic pollutants in coal chemical wastewater, solving the problems of low efficiency and high cost of traditional treatment methods, and achieving cost-effectiveness sewage treatment and promote the reuse and stability of the catalyst.

CN119215912AActive Publication Date: 2024-12-31TSINGHUA UNIVERSITY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411130648.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-31
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

There are difficult organic matter and heavy metals in coal chemical wastewater. The traditional treatment methods are inefficient and have high investment costs. The existing electron beam irradiation technology has a high cost and the pollution control effect needs to be improved.

Method used

A compound composite catalyst containing four metals La, Co, Bi and Ti is prepared, and the polymer organic compounds are efficiently degraded in aqueous solution by electron beam irradiation, and the catalyst is recycled and recycled.

Benefits of technology

It significantly improves the degradation effect of high-concentration organic compounds and long-chain polymer organic matter, reduces treatment costs, and does not add new hazardous waste and salinity risks, and promotes the industrialization process of irradiation and decontamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215912A_ABST
    Figure CN119215912A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation and irradiation degradation, and particularly relates to a composite catalyst, a preparation method thereof and application of the composite catalyst in irradiation degradation of coal chemical sewage. Specifically, the compound composite catalyst containing the four metals of La, Co, Bi and Ti is successfully prepared, tests prove that the compound composite catalyst can be used as an electron beam irradiation catalyst to improve the degradation effect on high-concentration organic compounds, refractory and long-chain high-molecular organic matters and the like, and organic pollutants can be thoroughly degraded to reach the emission standard; the economic efficiency is good, and the risk of newly adding hazardous wastes and salinity is avoided, so that the method has good practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation and radiation degradation, and specifically relates to a composite catalyst and a preparation method thereof and application in radiation degradation of coal chemical wastewater. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] The coal chemical industry is one of the key areas of my country's energy industry. However, in the process of coal chemical production, a large amount of wastewater discharge has become an environmental problem that needs to be solved urgently. These wastewaters contain a variety of harmful substances, such as heavy metals, organic matter and suspended solids, which pose a potential threat to the surrounding environment and water resources. Therefore, coal chemical wastewater treatment urgently needs to be paid attention to and solved to ensure the sustainability of industrial development and the health of the environment. Environmental protection: Coal chemical wastewater contains a large amount of harmful substances. Direct discharge will cause soil and water pollution and threaten the ecological balance. Implementing effective wastewater treatment is an important means to protect the environment and maintain ecological balance.

[0004] Coal chemical wastewater may contain some difficult-to-treat organic matter and heavy metals, such as benzene and cyanide, which are difficult to completely remove with traditional treatment methods and require more efficient treatment technologies. The introduction of advanced wastewater treatment technology requires a high investment cost. Some companies may be unwilling or unable to implement advanced wastewater treatment equipment due to economic considerations, which may become an obstacle to promoting technological upgrading.

[0005] Electron beam irradiation has been widely used and received attention as a new type of sewage treatment technology. Electron beam irradiation generates hydroxyl radicals to achieve rapid degradation of organic pollutants, and is an efficient method for industrial wastewater treatment and purification. Compared with traditional biochemical, physical and chemical treatment methods, electron beam irradiation has higher treatment efficiency and shorter treatment cycle, and does not require the addition of additional chemicals. Therefore, under the goal of zero discharge and sewage reuse, electron beam irradiation technology has become one of the important directions for the improvement of current sewage treatment technology. However, the inventors found that when electron beam irradiation is used for wastewater degradation treatment, there are problems such as high treatment costs and the pollution control effect still needs to be improved. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a composite catalyst and a preparation method thereof and an application thereof in irradiation degradation of coal chemical wastewater. Specifically, the present invention successfully prepares a compound composite catalyst containing four metals, La, Co, Bi, and Ti. It has been verified by experiments that it can be used as an electron beam irradiation catalyst to improve the degradation effect of high-concentration organic compounds, difficult-to-degrade, long-chain high-molecular organic matter, etc., and can completely degrade organic pollutants to emission standards, with good economic efficiency and no new hazardous waste and salinity risks. Therefore, based on the above research results, the present invention is completed.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a composite catalyst, wherein the composite catalyst is a compound containing at least four metals: La, Co, Bi, and Ti, wherein the LaCoO3 powder and Bi4Ti3O 12 The mass ratio of the nanosheets is 0.5-5:2-10.

[0009] The second aspect of the present invention provides a method for preparing the composite catalyst, the preparation method comprising:

[0010] S1、Bi4T i3 O 12 Preparation of nanosheets: Mix Bi2O3 and TiO2, grind them together, calcine the mixture, and cool and dry them to obtain nanosheets.

[0011] S2. Preparation of LaCoO3 powder: adding lanthanum source and cobalt source into water for heating treatment, then adding citric acid and standing until gel is formed; calcining the obtained gel to obtain;

[0012] S3. Preparation of composite catalyst: Bi4Ti3O 12 The nanosheets and LaCoO3 powder are dispersed in methanol, mixed evenly, and dried to obtain the product.

[0013] The third aspect of the present invention provides the use of the above composite catalyst in irradiation degradation wastewater treatment.

[0014] Wherein, the sewage may be coal chemical sewage.

[0015] Compared with the existing technical solutions, the above one or more technical solutions have the following beneficial effects:

[0016] The above technical scheme provides a compound composite catalyst containing four metals, La, Co, Bi, and Ti. Experimental verification shows that it can utilize radiation energy to catalyze the efficient degradation of high-molecular organic compounds in aqueous solution, while effectively realizing the repeated recycling of the catalyst and having good stability, which further promotes the industrialization process of radiation decontamination. Therefore, it has good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0018] Figure 1 This is an electron microscope image of the composite catalyst prepared in Example 1 of the present invention; wherein 1-LaCoO3, 2-Bi4Ti3O 12 . DETAILED DESCRIPTION

[0019] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0020] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0021] In a typical embodiment of the present invention, a composite catalyst is provided, wherein the composite catalyst is a compound containing at least four metals: La, Co, Bi, and Ti. Specifically, the composite catalyst is composed of LaCoO3 powder and Bi4T i3 O 12 The LaCoO3 powder and Bi4Ti3O 12 The mass ratio of the nanosheets is 0.5-5:2-10; further 1-2:3-5; further 1.28:4.01.

[0022] In another specific embodiment of the present invention, a method for preparing the composite catalyst is provided, the preparation method comprising:

[0023] S1、Bi4T i3 O 12Preparation of nanosheets: Mix Bi2O3 and TiO2, grind them together, calcine the mixture, and cool and dry them to obtain nanosheets.

[0024] S2. Preparation of LaCoO3 powder: adding lanthanum source and cobalt source into water for heating treatment, then adding citric acid and standing until gel is formed; calcining the obtained gel to obtain;

[0025] S3. Preparation of composite catalyst: Bi4Ti3O 12 The nanosheets and LaCoO3 powder are dispersed in methanol, mixed evenly, and dried to obtain the product.

[0026] Wherein, in the step S1, the mass ratio of Bi2O3 and TiO2 is 2-10:0.5-3, further 4-7:1-3; further 6:2.76; the pulverization can be carried out by a grinding process, in order to improve the particle dispersion during the grinding process and promote the uniform mixing of the raw materials; and / or play a fluxing effect during the calcination process, so further, the present invention adds additives to Bi2O3 and TiO2, and the additives can be at least one of sodium salt, potassium salt, lithium salt or ammonium salt; further, the additive is NaCl or KCl; the amount of the additive added is controlled to be 1-10% (w / w) of the mixture.

[0027] The specific conditions for calcination are: the heating rate is controlled at 2-5°C / min, the calcination end point temperature is controlled at 700-900°C, more preferably 800-900°C, and the end point temperature is maintained for 2-4h.

[0028] In step S2, the lanthanum source and the cobalt source are at least one of the oxides, chlorides, nitrates, carbonates, etc. of lanthanum and cobalt; further, lanthanum nitrate (La(NO3)3·6H2O) and cobalt nitrate (Co(NO3)2·6H2O) are selected as the lanthanum source and the cobalt source, respectively.

[0029] The mass ratio of the lanthanum source, the cobalt source and the citric acid is 10-30:1-5:10-20, further 20.71:3.17:16.80.

[0030] The specific calcination conditions include: pre-calcining at 200-300°C (preferably 250°C) for 3-5h, then heating at a rate of 5-10°C / min, the end point temperature of calcination is 700-900°C (preferably 800-900°C), and maintaining the end point temperature for 3-5h (preferably 4-5h).

[0031] In step S3, the LaCoO3 powder and Bi4Ti3O 12 The mass ratio of the nanosheets is 0.5-5:2-10; further 1-2:3-5; further 1.28:4.01.

[0032] In another specific embodiment of the present invention, there is provided the use of the above composite catalyst in irradiation degradation wastewater treatment.

[0033] Wherein, the sewage may be coal chemical sewage.

[0034] Specifically, the specific method of the application includes: adding the above-mentioned composite catalyst into coal chemical wastewater and irradiating it with an electron beam.

[0035] The dosage of the composite catalyst is 0.01-0.1 g / L, further 0.5 g / L.

[0036] The specific conditions of the irradiation treatment are: electron beam irradiation energy is 1-10 MeV (preferably 1-5 MeV), irradiation beam intensity is 10-200 mA (preferably 10-100 mA), irradiation dose is 0.5-30 kGy, and irradiation treatment time is 0.5-1 min.

[0037] The coal chemical wastewater is industrial wastewater generated in the coal chemical production process. The treatment process of the present invention can significantly reduce the COD of coal chemical wastewater. At the same time, the iron-based metal organic framework / titanium dioxide composite material prepared above can be recycled repeatedly, has good stability, further reduces the processing cost, and promotes the industrialization process of irradiation decontamination.

[0038] The present invention is further described below in conjunction with specific examples. The following examples are only for explaining the present invention and are not intended to limit its contents. Any simple modification, equivalent changes and modifications made to the implementation methods according to the technical essence of the present invention are within the scope of the technical solution of the present invention. The same batch of coal chemical wastewater is used in each embodiment, and its initial COD is 630 mg / L.

[0039] Example 1

[0040] (1)Bi4Ti3O 12 Preparation of nanosheets. 6.0g Bi2O3 and 2.76g TiO2 were mixed, 0.88g NaCl additive was added and ground for 2h; the mixture was calcined at a heating rate of 2℃ / min and an end point temperature of 800℃, which was maintained for 2h. After cooling, Bi4Ti3O 12 The nanosheets were dried at 60 °C.

[0041] (2) Preparation of LaCoO3 powder. Add 20.71g La(NO3)3·6H2O and 3.17g Co(NO3)3·6H2O to 100ml water, heat to 60℃ and stir, then add 16.80g citric acid monohydrate to the reaction system and let it stand until a gel is formed. Calcine the gel by pre-calcining the gel at 250℃ in a muffle furnace for 4h, then heating at a rate of 5℃ / min, and the final temperature of calcination is 800℃, which is maintained at the final temperature for 4h. After calcination, a black solid powder LaCoO3 powder is obtained.

[0042] (3) Preparation of composite catalyst. 1.28 g LaCoO3 powder and 4.01 g Bi4Ti3O 12 The nanosheets were dispersed in 20 ml of methanol and uniformly mixed; stirring was continued at room temperature and the mixture was dried in an oven at 60° C. for 12 h to obtain a compound catalyst containing four metals: La, Co, Bi and Ti.

[0043] (4) The composite material powder was added to the pretreated coal chemical wastewater, the COD of which was 630 mg / L, and the addition amount was 0.05 g / L. Electron beam irradiation was performed, the energy of the electron beam irradiation was 5 MeV, the beam intensity was 10 mA, the absorbed dose was 5 kGy, and the irradiation treatment time was 60 seconds.

[0044] Example 2

[0045] The process is carried out in accordance with Example 1, except that in step 1, the amount of TiO2 is changed from 2.76 g to 5.52 g, and the other steps are the same as those in Example 1.

[0046] Example 3

[0047] The process was carried out in accordance with Example 1, except that in step 2, the gel was not pre-calcined, and the temperature was directly increased at a rate of 5°C / min, the final temperature of the calcination was 800°C, and the final temperature was maintained for 4 hours. After calcination, a black solid powder LaCoO3 powder was obtained. The other steps were the same as in Example 1.

[0048] Example 4

[0049] The process is carried out in accordance with Example 1, except that in step 3, Bi4Ti3O 12 The mass of the nanosheets changed from 4.01 g to 10.03 g, and the other steps were the same as in Example 1.

[0050] Example 5

[0051] The process is carried out in accordance with Example 1, except that in step 2, Bi4Ti3O 12The calcination temperature of the nanosheets was adjusted differently, the heating rate was 3°C / min, the terminal temperature of the calcination was 680°C, and the terminal temperature was maintained for 2 hours. The rest was the same as in Example 1.

[0052] Example 6

[0053] The process was carried out in accordance with Example 1, except that in step 2, the mass of citric acid monohydrate added was different, namely 1 g. The rest was the same as in Example 1.

[0054] Example 7

[0055] Without adding a catalyst, the biochemical wastewater was subjected to the same irradiation process as step 4 in Example 1.

[0056] Table 1 Comparison of sewage degradation rates in the examples

[0057] Case COD(mg / L) COD degradation rate Sewage original 630 / Example 1 238 62.2% Example 2 293 53.5% Example 3 254 59.7% Example 4 296 53.0% Example 5 286 54.6% Example 6 268 57.5% Example 7 427 32.2%

[0058] From the COD removal rate of sewage in Table 1, it can be seen that the composite catalyst obtained in Example 1 has the best catalytic activity, and significantly improves the degradation of COD compared to the single irradiation of the electron beam. The composite catalyst prepared in Example 1 of the present invention can be repeatedly used more than 20 times, and the catalyst can be recycled and reused more than 20 times after drying and repeated sintering.

[0059] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A composite catalyst, characterized in that: The composite catalyst is a compound containing at least four metals: La, Co, Bi, and Ti. i3 O 12 The LaCoO3 powder and Bi4T i3 O 12 The mass ratio of the nanosheets is 0.5-5:2-10.

2. The method for preparing the composite catalyst according to claim 1, characterized in that: The preparation method comprises: S1、Bi4T i3 O 12 Preparation of nanosheets: Mix Bi2O3 and TiO2, grind them together, calcine the mixture, and cool and dry them to obtain nanosheets. S2. Preparation of LaCoO3 powder: adding lanthanum source and cobalt source into water for heating treatment, then adding citric acid and standing until gel is formed; calcining the obtained gel to obtain; S3. Preparation of composite catalyst: Bi4Ti3O 12 The nanosheets and LaCoO3 powder are dispersed in methanol, mixed evenly, and dried to obtain the product.

3. The preparation method according to claim 2, characterized in that: In the step S1, the mass ratio of Bi2O3 to TiO2 is 2-10:0.5-3; and the pulverization is performed by a grinding process.

4. The preparation method according to claim 2, characterized in that: In the step S1, an additive is added to Bi2O3 and TiO2, wherein the additive is at least one of a sodium salt, a potassium salt, a lithium salt or an ammonium salt; further, the additive is NaCl or KCl; and the amount of the additive added is controlled to account for 1-10% of the mixture; The specific conditions of calcination are: the heating rate is controlled at 2-5°C / min, the calcination end temperature is controlled at 700-900°C, and the end temperature is maintained for 2-4h.

5. The preparation method according to claim 2, characterized in that: In step S2, the lanthanum source and the cobalt source are at least one of oxides, chlorides, nitrates, carbonates, etc. of lanthanum and cobalt; further, lanthanum nitrate and cobalt nitrate are selected as the lanthanum source and the cobalt source, respectively.

6. The preparation method according to claim 2, characterized in that: In the step S2, the mass ratio of the lanthanum source, the cobalt source and the citric acid is 10-30:1-5:10-20, and further is 20.71:3.17:16.

80.

7. The preparation method according to claim 2, characterized in that: In step S2, the specific calcination conditions include: pre-calcining at 200-300°C for 3-5h, then heating at a rate of 5-10°C / min, the terminal temperature of calcination is 700-900°C, and maintaining at the terminal temperature for 3-5h.

8. The preparation method according to claim 2, characterized in that: In step S3, the LaCoO3 powder and Bi4Ti3O 12 The mass ratio of the nanosheets is 0.5-5:2-10; further 1-2:3-5; further 1.28:4.

01.

9. Use of the composite catalyst according to claim 1 or the composite catalyst prepared by the preparation method according to any one of claims 2 to 8 in irradiation degradation wastewater treatment.

10. The use according to claim 9, characterized in that: The sewage is coal chemical sewage; Furthermore, the specific method of the application includes: adding the composite catalyst into coal chemical wastewater and irradiating it with an electron beam; Wherein, the dosage of the composite catalyst is 0.01-0.1 g / L, further 0.5 g / L; The specific conditions of the irradiation treatment are: electron beam irradiation energy is 1-10 MeV, irradiation beam intensity is 10-200 mA, irradiation dose is 0.5-30 kGy, and irradiation treatment time is 0.5-1 min.

Citation Information

Patent Citations

  • Layered perovskite structural ceramic and preparation method thereof

    CN102875146A

  • Catalytic ozonation water treatment and impurity removal technology based on enhanced electron transfer efficiency

    CN109607743A

  • Composite catalyst for electron beam sewage treatment as well as preparation method and application of composite catalyst

    CN113231059A

  • Method for producing oxysilane compound

    JP2002371074A